Rancang Bangun Web E-Commerce Menggunakan Metode Collaborative Filtering (Study Kasus: Toko aksesories tata) - Aisha, Dita; Dwi Indriyanti, Aries; Heru Mujianto, Ahmad (Inovate, 2020)
E-Commerce is one of the alternative choices for a store that is used as a medium of information in order to facilitate interaction between sellers and consumers. The number of products, the variety of products in an e-commerce, often makes consumers feel confused about choosing the product they need. This resulted in a repetitive and time-consuming transaction process. Consumers are often confused about finding information on the rating of the product the user wants to buy. In this study, a Web e Commerce was created which was able to provide recommendations automatically to the user. The method used is the Collaborative Filtering method using Addjusted Cossine Similarity as a tool or method of calculating the similarity between users, then the weigted sum algorithm as the prediction calculation. Collaborative Filtering is used to assist users in selecting the appropriate item based on ratings given by other users. Keywords: Collaborative Filtering (CF), Recommendations, E-commerce Website.